Autoarte (2017)
"The Auto-arte school proposes an educational center, which includes the different trades that works in the sector, generating neutral space that allows to unify the existing communities of the San Felipe neighborhood. Through an academic environment, collaborative work is proposed, generating points of convergence in which students can be involved in activities beyond their own and recognize the contributions of other trades. The design is based on the spaces for social interaction, acting as a hybrid building, container of the different spaces of exchange. The connections between opposites are given by the spatialities, creating thresholds of different scales and identities, allowing a distinctive but fluid transition between the automotive and the artistic community. This building is projected as a trainer for the San Felipe neighborhood, it takes advantage of the environment and improve it trough education".-- Tomado del Formato de Documento de Grado.